Uses of the West : security and the politics of order - Hellmann, Gunther, 1960-; Herborth, Benjamin (Cambridge : Cambridge University Press, 2017)
The notion of'the West' is commonly used in politics, the media, and in the academic world. To date, our idea of'the West' has been largely assumed and effective, but has not been examined in detail from a theoretical perspective. Uses of'the West' combines a range of original and topical approaches to evaluate what'the West' really does, and how the idea is being used in everyday political practice. This book examines a range of uses of'the West', and traces how'the West' works in a broad array of conceptual and empirical contexts, ranging from the return of geopolitics - via a critical review of the debates surrounding Samuel Huntington's Clash of Civilization thesis - to the question of the future of'the West'. Analysis extends further to the repercussions of the war on terror on Western democracy and the processes of delineating the Western from the non-Western, as well as observations of the institutional transformations of Western order.
Title from publisher's bibliographic system (viewed on 31 Jan 2017).
Keywords: Civilization, Western